A simple approach to form Ge nanocrystals embedded in amorphous Lu2O3 high-k gate dielectric by pulsed laser ablation - Yuan, C. L. (2013)
We have successfully developed a novel method to fabricate the memory structure of Ge nanocrystals embedded in amorphous Lu2O3 high-k dielectric using pulsed laser ablation. The mean size and aerial density of the Ge nanocrystals are estimated to be about 9 nm and 7 × 1011 cm−2, respectively. Good performances in terms of large memory window and long data retention were observed. Our preparation method is simple, fast and economical.